Epidemiology of breast cancer in Zaporizhzhia region from 2011 to 2016. - A. І. Shevchenko; O. М. Levyk; A. S. Alieshchenko (Zaporozhye State Medical University, 2018)
Breast cancer is the most important problem of modern oncology. The aim of our study was to analyze morbidity and survival of patients with breast cancer in the Zaporizhzhia region since 2011 to 2016 years and to investigate the state of care in this patient's category. Materials and methods. The work is based on the analysis of survival of 4259 patients with the I-IV stage, who were hospitalized at the department of breast pathology at Zaporizhzhia Regional Clinical Oncology Dispensary in the AIA from 2011 to 2016. Results. In the Zaporizhzhia region in 2016, 86.0 cases per 100 thousand people were identified. A gradual increase in the number of patients with later stages detection of the disease was noted. The mortality of the female population from the breast cancer in Zaporizhzhia region ranks first in the overall structure of female mortality from malignant neoplasms and is 33.9 per 100.000 population in 2016 year. The maximum survival rate of patients with the WPH was registered in 2016 - 54.9 per 100 thousand of the population. Conclusions. When carrying out the analysis of the incidence of the breast cancer in Zaporizhzhia and Zaporizhzhia region for 2011-2016 years revealed an increase in morbidity by more than 11.3 per 100 thousand population. There remains a high rate of detectability of high stages of the breast cancer, which indicates the need to improve screening programs to identify breast tumors.